The Impact of Exercise and Virtual Reality Executive Function Training on Cognition Among Heavy Drinking Veterans With Traumatic Brain Injury: A Pilot Feasibility Study - Pennington, David L.; Reavis, Jill V.; Cano, Monique T.; Walker, Erica; Batki, Steven L. (Frontiers in Behavioral Neuroscience, 2022)
Executive function (EF) underlies self-control deficits in alcohol use disorder (AUD) and traumatic brain injury (TBI). Cognitive training is a promising adjunctive treatment targeting TBI- and AUD- related cognitive dysfunction. However, major limitations related to compliance and generalizability in the field of cognitive training exist. Physical activity is associated with enhanced cognitive performance across several executive functions and may enhance the benefits of cognitive training. Virtual reality provides multisensory embodied experiences which are likely to engage brain networks more efficiently than standard cognitive training systems, ultimately resulting in greater near- and far-transfer effects. This pilot study aimed to obtain feasibility data and a preliminary assessment of an enriched virtual reality (VR) EF training (EFT) intervention combined with exercise (NCT03786276). Using an 8-week randomized adaptive design study, 30 AUD treatment seeking U.S. Veterans completed nine sessions of exercise-only (n = 15) or gameplay control (n = 15) over 3 weeks, followed by a week-4 repeat assessment in Phase 1. Twenty-three participants completed and moved onto Phase II, where they completed up to nine sessions of VR-EFT plus exercise and completed a week-8 end-of-study assessment. Primary outcomes included feasibility to retain participants, usability, and satisfaction of using VR-EFT. Secondary and exploratory outcomes included within group assessment of change in cognitive function, alcohol use, alcohol craving, and post-concussive symptoms among the three treatment conditions.VR-EFT was feasible with moderate usability and high acceptability ratings.The most common VR-related adverse effect was motion sickness (n = 2/16, 12.5%). The VR-EFT condition was associated with significant improvement in inhibition-switching and visual scanning (both p < 0.05) during Phase II. Exercise-only was associated with significant improvements in cognitive inhibition, cognitive flexibility, reductions in alcohol craving, and number of standard alcohol drinks per week (all p ≤ 0.05). The gaming-control condition was associated with improvement in cognitive flexibility and visuospatial immediate recall (both p < 0.05) during Phase 1. Recruitment and retention of U.S. veterans with AUD and TBI into an exercise plus VR-EFT intervention is feasible, but technological barriers may impact usability. VR-EFT was associated with improvement in executive function domains that were targeted in as little as 3-week and nine sessions of VR-EFT exposure. Results are promising and indicate the need for a larger controlled investigation to assess the efficacy of VR-EFT to enhance treatment outcomes among AUD treatment-seeking U.S. veterans with co-occurring AUD and TBI. Clinical Trial Registration www.ClinicalTrials.gov, Identifier: NCT03786276.